(untitled) (Rudarsko-geološko-naftni zbornik, 2019)
This study investigates the effect of variations of coal dust particles size on the rate of burning of coal dust particles in a 2-liter closed chamber. Coal dust was selected from three different mines with different sizes (149μm, 125μm, 105μm, 74μm, 63μm, 53μm, 44μm, 37μm) for explosion testing in a closed chamber of 2-liters. In this analysis, the concentration of coal dust was considered constant (10000 g/m3), all tests were carried out at a pressure of 1.5 bar and the initial tem- perature was 25 °C. To calculate the burning rate, the explosion severity parameters of each sample, such as the maxi- mum explosion pressure, the maximum rate of increase in pressure, and the explosion index must be determined during various tests. The results of the experiments show that by variating the size of the coal dust particles, the burning rate of the particles also changes and there is an inverse relationship between them. Coal dust particles with dimensions of 44μm and 37 μm have a higher burning velocity than other dimensions. Thus, with a reduction in the size of coal dust particles, the burning velocity of coal dust increases. The outcomes acquired in this examination are not just valuable in developing information on coal dust explosion processes, but also improve the measures needed to prevent coal dust explosions in coal mines.